STATIC MIXERS IN FLUSHING FLUID CIRCULATION SYSTEMS OF DRILLING RIGS - Biletsky, V. S.; Mishchuk, Yu. S.; Kuznetsova, Yu. I. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The work of three static mixer designs in flushing fluid circulation systems of drilling rigs was studied taking into account the basic parameters of drilling mud. Modelling was carried out, and parametric slurry fields were obtained in the pipe work area, that is in a static mixer installation site and in the area of pipeline behind it. The following models were obtained: velocity fields, vorticity fields, turbulence intensity fields, scale turbulence fields along the travel path. Graphs of the parameters changes regarding the tube axis were plotted. The comparative analysis of patterns and curves was carried out. The rational design of static mixer for obtaining of optimum mud mixing technology features is grounded.